A new tool for creative content evaluation: young children’s participation - Mohd Yusoff, Yusrita; Ruthven, Ian; Landoni, Monica; Shaari, Nassiriah; Alwi, Asmidah (Faculty of Computing, Universiti Teknologi Malaysia, 2016)
This paper discusses young children’s participation aged four to six-year-old (kindergarten in Malaysia) in developing a new tool for creative content evaluation.A preliminary study was conducted in one university kindergarten in Malaysia to refine the design of existing evaluation tool, Fun Semantic Differential Scales (FSDS) within Malaysian kindergarteners’ context.The study aims to validate pictures used in the existing FSDS.